The parasitoid complex of diamondback moth, Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), in Canada: impact and status. Issue 1 (25th January 2022) - Mason, Peter G.; Dancau, Tina; Abram, Paul K.; Noronha, Christine; Dixon, Peggy L.; Parsons, Carolyn K.; Bahar, M.H.; Bennett, Andrew M.R.; Fernández-Triana, José; Brauner, Andrea M.; Clarke, Peggy; Thiessen, Jason; et al.
Abstract: Diamondback moth, Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), a globally important pest of Brassicaceae crops, migrates into all provinces of Canada annually. Life tables were used to determine the mortality levels contributed by the parasitoid complexes associated with diamondback moth in British Columbia, Ontario, Prince Edward Island, and insular Newfoundland. Overall, diamondback moth populations showed high generational mortality (> 90%) in all provinces, although parasitism levels were generally low. The net reproductive rate of increase in diamondback moth was less than 1.0 (populations declined) in both years in British Columbia and in each of two years in Newfoundland and Ontario, but it was greater than 1.0 in all three years in Prince Edward Island. Lower parasitism levels were found in Prince Edward Island (3.0–6.3%) compared with other provinces (8.4–17.6%, except one year in British Columbia). Diadegma insulare was the main larval parasitoid found; it was present in all provinces. Microplitis plutellae was present in all provinces except British Columbia. Oomyzus sokolowskii was found in British Columbia and Ontario. The parasitoid community documented from sentinel sampling was less diverse than that found through destructive sampling. Hypotheses are provided to explain the presence of major parasitoids. Increasing larval parasitism would have the largest effect on diamondback moth population growth in Canada.